2017
DOI: 10.1016/j.bbamcr.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The Extended-Synaptotagmins

Abstract: The extended-synaptotagmins (tricalbins in yeast) derive their name from their partial domain structure similarity to the synaptotagmins, which are characterized by an N-terminal membrane anchor and cytosolically exposed C2 domains. However, they differ from the synaptotagmins in localization and function. The synaptotagmins tether secretory vesicles, including synaptic vesicles, to the plasma membrane (PM) via their C2 domains and regulate their Ca2+ triggered exocytosis. In contrast, the extended-synaptotagm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 47 publications
(89 reference statements)
1
86
0
Order By: Relevance
“…All three E-Syts comprise an N-terminal hydrophobic hairpin through which they are anchored to the ER (Giordano et al, 2013;Saheki et al, 2016). This region is followed by a synaptotagmin-like mitochondrial lipid-binding protein (SMP) domain (Lee & Hong, 2006;Kopec et al, 2010;Toulmay & Prinz, 2012;Schauder et al, 2014) and multiple C2 domains, five in E-Syt1 and three in E-Syt2 and E-Syt3 (see Fig 1A; Min et al, 2007;Saheki & De Camilli, 2017b). As shown by the crystal structure, the first two C2 domains of E-Syt2 (C2AB) are arranged in tandem (Schauder et al, 2014;Xu et al, 2014) and a similar arrangement is predicted for the C2AB domains of E-Syt1 and E-Syt3.…”
Section: Introductionmentioning
confidence: 99%
“…All three E-Syts comprise an N-terminal hydrophobic hairpin through which they are anchored to the ER (Giordano et al, 2013;Saheki et al, 2016). This region is followed by a synaptotagmin-like mitochondrial lipid-binding protein (SMP) domain (Lee & Hong, 2006;Kopec et al, 2010;Toulmay & Prinz, 2012;Schauder et al, 2014) and multiple C2 domains, five in E-Syt1 and three in E-Syt2 and E-Syt3 (see Fig 1A; Min et al, 2007;Saheki & De Camilli, 2017b). As shown by the crystal structure, the first two C2 domains of E-Syt2 (C2AB) are arranged in tandem (Schauder et al, 2014;Xu et al, 2014) and a similar arrangement is predicted for the C2AB domains of E-Syt1 and E-Syt3.…”
Section: Introductionmentioning
confidence: 99%
“…• Mediate tethering of the ER to the plasma membrane (PM) and lipid transfer (extended synaptotagmins) [27], • Recruit proteins to membranes and are involved in cell signaling (copines and RASAL1) [28][29][30], and, • Phosphorylate inositol phospholipids, thereby influencing intracellular processes like signal transduction or clathrin-mediated endocytosis (PI3KC2s) [31].…”
Section: Introductionmentioning
confidence: 99%
“…The tricalbin proteins (Tcb1/2/3) are orthologs of the mammalian extended-synaptotagmins (E-Syts) and the plant synaptotagmins (SYTs) (Pé rez-Sancho et al, 2016;Saheki and De Camilli, 2017b). Tcbs are likely anchored to the ER membrane by a hairpin sequence (Giordano et al, 2013;Saheki and De Camilli, 2017b) (Figure 2A) similar to those found in ER morphogenetic proteins such as reticulons (Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 93%